2018
DOI: 10.15226/jnhfs.2018.001142
|View full text |Cite
|
Sign up to set email alerts
|

Calcium and Magnesium Levels Change in Relationship to Variations in Usual Dietary Nutrient Intake

Abstract: Objective: Changes in nutrient intake induce changes in calcium and magnesium metabolism. However, studies dealing with these changes were usually performed by addition of one specific nutrient to initiate changes in either calcium or magnesium in only one biological fluid, usually blood plasma or urine. We were interested in evaluating changes in both calcium and magnesium levels in several biological fluids simultaneously in relationship to usual intake of a wide range of dietary nutrients since this type of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 121 publications
(137 reference statements)
0
1
0
Order By: Relevance
“…Similarly, many older studies have demonstrated that urinary Ca decreases with the intake of phosphorus supplements [46,47]. According to Henkin, in his studies about Calcium and Magnesium Levels Change in Relationship to Variations in Usual Dietary Nutrient Intake, it has been shown negligible variations in urinary calcium excretion with the high phosphorus intake [48].…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, many older studies have demonstrated that urinary Ca decreases with the intake of phosphorus supplements [46,47]. According to Henkin, in his studies about Calcium and Magnesium Levels Change in Relationship to Variations in Usual Dietary Nutrient Intake, it has been shown negligible variations in urinary calcium excretion with the high phosphorus intake [48].…”
Section: Discussionmentioning
confidence: 99%